Self-Confidence and Psychological Well-Being on Employability of Vocational High School Students - Dinda Khairunnisa; Herlina Siwi Widiana; Hadi Suyono (Psikostudia : Jurnal Psikologi, 2022)
This study aims to empirically examine the effect of self-confidence, psychological well-being on employability of vocational students. The subjects in this study were students of SMK Negeri 2 Langsa City (N=42). The sampling technique used cluster random sampling. This study uses a quantitative method with employability, self-confidence, and psychological well-being scales as a data collection tool. The research data were analyzed using multiple regression analysis techniques with the help of SPSS version 25.0 for windows. Based on the analysis process, the results showed that the major hypothesis was accepted, namely that there was a very significant influence on self-confidence and psychological well-being on employability. The analysis on the minor hypothesis is also accepted, namely that there is a significant effect on self-confidence on employability and there is a very significant effect on psychological well-being on employability. This finding shows that self-confidence and psychological well-being have a contribution in influencing employability of students at SMK Negeri 2 Langsa City, and psychological well-being is the most dominant factor in influencing employability Penelitian ini bertujuan untuk menguji secara empiris pengaruh kepercayaan diri, psychological well-being terhadap employability pada siswa SMK. Subjek dalam penelitian ini ialah siswa SMK Negeri 2 Kota Langsa (N=42). Teknik pengambilan sampel  menggunakan cluster random sampling. Penelitian ini menggunakan metode kuantitatif dengan skala employability, kepercayaan diri, dan psychological well-being sebagai alat pengumpulan data. Data penelitian dianalisis menggunakan teknik analisis regresi berganda dengan bantuan program SPSS versi 25.0 for windows. Berdasarkan proses analisis, diperoleh hasil yang menunjukkan hipotesis mayor diterima, yaitu terdapat pengaruh yang sangat signifikan pada kepercayaan diri dan psychological well-being terhadap employability. Analisis pada hipotesis minor juga diterima, yaitu terdapat pengaruh yang signifikan pada kepercayaan diri terhadap employability dan terdapat pengaruh yang sangat signifikan pada psychological well-being terhadap employability. Temuan ini menunjukkan bahwa kepercayaan diri dan psychological well-being memiliki kontribusi dalam memengaruhi employability pada siswa SMK Negeri 2 Kota Langsa, dan psychological well-being menjadi faktor yang paling dominan dalam memengaruhi employability.